Symbolic and affective motives, constraints and self-efficacy among Romanian car buyers - Mădălina Bălău (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2019)
Cars have long been considered goods that symbolize status, yet few studies integrate the impact of symbolic and affective motives on the car buying decisions, with even fewer studies focusing on the influence of these motives on Eastern European consumers' buying behaviour. The aim of this paper is to propose and test an integrative model, derived from the MOA model, which accounts for consumer motives (instrumental, symbolic and affective), constraints and abilities. The model is tested on a sample of Romanian consumers owning a driving licence. The data analysis was based on structural equation modelling. Findings indicate that symbolic and instrumental car use motives positively influence the intention to buy a car sooner, while affective motives have a negative influence, leading consumers to postpone the intention to buy a car. Results also show a significant positive effect of self-efficacy on intention implementation. Thus, the stimulation of symbolic motives may increase car buying intentions, while the presence of affective motives may lead consumers to still enjoy their current car. The paper contributes to expanding our understanding of consumer behaviour through an integrative model, which includes psychological motives, external factors and consumer abilities.
Keywords: D11; D12; M31; 650; symbolic motives; affective motives; instrumental motives; car buying; MOA model; self-efficacy